Correction: Multimodal X-ray microanalysis of a UFeO4 particle: evidence for the environmental stability of ternary U(v) oxides from depleted uranium munitions testing. Issue 9 (12th August 2020) - Crean, Daniel E.; Stennett, Martin C.; Livens, Francis R.; Grolimund, Daniel; Borca, Camelia N.; Hyatt, Neil C.
Abstract : Correction for 'Multimodal X-ray microanalysis of a UFeO4 particle: evidence for the environmental stability of ternary U(v ) oxides from depleted uranium munitions testing' by Daniel E. Crean et al., Environ. Sci.: Processes Impacts, 2020, DOI: ; 10.1039/d0em00243g .